Factors defining expertise in screening colonoscopy - Patel, Kinesh; Pinto, Anna; Faiz, Omar; Rutter, Matt; Thomas-Gibson, Siwan (Endoscopy International Open, 2017)
Background and study aims There is very little literature defining characteristics of expert endoscopists. It is hypothesised that previously undetermined human factors may correlate with high performance in screening colonoscopists. The aim of this study was to determine factors contributing towards expertise in screening colonoscopy.Materials and methods A focus group was used to hypothesise skills considered to be relevant to high performance in colonoscopy. The skills were then ranked in order of importance by an independent group of screening colonoscopists for both diagnostic and therapeutic colonoscopy. Twenty screening colonoscopists subsequently participated in individual semi-structured interviews to explore participants’ views of expertise and the factors contributing to it. Data extracted from the interview transcripts were used to identify the thematic framework associated with expertise.Results The 5 initial highest-ranked themes were low complication rates, high adenoma detection rates, interpersonal skills with staff, communication skills, and manner with patients. Interviewees considered technical skills (20/20), previous experience of colonoscopy (19/20), judgment/decision-making (18/20), communication (18/20), teamwork (15/20), resources (11/20) and leadership (8/20) to be the most important themes related to expertise.Conclusions Both technical and non-technical abilities are considered essential components of expertise by experienced colonoscopists. Further research into targeted interventions to improve the rate of acquisition of these skills in training endoscopists may be useful in improving performance.